Togo : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Togo during 1991-96. From 1991 to 1993, real GDP experienced a cumulative decline of 22 percent. The tertiary sector was particularly hard hit, falling by 38 percent, as the political turmoil provoked an exodus of traditional regional services activity, previously based in Togo, to neighboring countries; thus commerce and tourism, and transport and communications value added fell by a cumulative 47.7 percent and 50.0 percent, respectively. The secondary sector contracted by some 35.0 percent over the period, as phosphate production declined in 1992 and 1993.